Pengaruh Penerapan Model Problem-Based Learning melalui LKPD Berbasis Kebudayaan Daerah terhadap Kemampuan Numerasi Siswa Kelas X SMAN 3 Mataram - Nisa Husniatissibhi; Ketut Sarjana; Eka Kurniawan (Griya Journal of Mathematics Education and Application, 2026)
Numeracy skills are essential competencies that enable students to understand, process, and interpret mathematical information in various real-life contexts. However, students’ numeracy skills still need improvement, particularly in statistics learning. This study aimed to determine the effect of implementing the Problem-Based Learning (PBL) model through local culture-based Student Worksheets (LKPD) on the numeracy skills of tenth-grade students at SMAN 3 Mataram. This study employed a quasi-experimental method using a posttest-only control group design. The sample consisted of 78 students divided into an experimental class and a control class. Numeracy data were collected using a test instrument that had been validated by experts. The findings showed that students who learned through PBL with local culture-based LKPD achieved higher numeracy skills than those who received direct instruction. The results of the independent sample t-test indicated a significant difference between the two groups, with a very high level of instructional effect. These findings suggest that the implementation of PBL through local culture-based LKPD is effective in supporting the improvement of students’ numeracy skills in statistics learning.